An accurate model for the computation of the dose of protons in water. (June 2017) - Embriaco, A.; Bellinzona, V.E.; Fontana, A.; Rotondi, A.
Highlights: A fast and accurate model for the dose calculation of protons in water is presented. The exact description of electromagnetic interactions allows for a minimal number of parameters for the nuclear part. The longitudinal profile is fully calculated using a new formula for energy loss, straggling and nuclear build-up. The 2D lateral profile is reconstructed from a non gaussian distribution with the Papoulis algorithm. The results are compared with validated MC simulations both with a single beam and with a Field Size Factor test. Abstract: Purpose: The accurate and fast calculation of the dose in proton radiation therapy is an essential ingredient for successful treatments. We propose a novel approach with a minimal number of parameters. Methods: The approach is based on the exact calculation of the electromagnetic part of the interaction, namely the Molière theory of the multiple Coulomb scattering for the transversal 1D projection and the Bethe-Bloch formula for the longitudinal stopping power profile, including a gaussian energy straggling. To this e.m. contribution the nuclear proton-nucleus interaction is added with a simple two-parameter model. Then, the non gaussian lateral profile is used to calculate the radial dose distribution with a method that assumes the cylindrical symmetry of the distribution. Results: The results, obtained with a fast C++ based computational code calledMONET (MOdel of ioN dosE for Therapy), are in very good agreement with the FLUKA MC code, within a few percent in the worst case. Conclusions: This study provides a new tool for fast dose calculation or verification, possibly for clinical use.